Thoracic spine pain in the general population: Prevalence, incidence and associated factors in children, adolescents and adults. A systematic review - Briggs, Andrew; Smith, Anne; Straker, Leon; Bragge, P. (Biomed Central Ltd, 2009)
Background. Thoracic spine pain (TSP) is experienced across the lifespan by healthy individuals and is a common presentation in primary healthcare clinical practice. However, the epidemiological characteristics of TSP are not well documented compared to neck and low back pain. A rigorous evaluation of the prevalence, incidence, correlates and risk factors needs to be undertaken in order for epidemiologic data to be meaningfully used to develop evidence-based prevention and treatment recommendations for TSP.